Regulation of the Interferon Response by lncRNAs in HCV Infection - Valadkhan, Saba; Fortes, Puri (Frontiers in Microbiology, 2018)
The interferon (IFN) response is a critical component of the innate immunity antiviral pathways in mammalians. IFN signaling results in increased expression of cellular factors that block key steps in the viral replication cycle. Many IFN-induced antiviral factors act through decreasing viral entry, replication, transcription, translation, packaging and release. However, these effects are also deleterious for the viability of the cell, which necessitates a tight control over the magnitude and duration of the IFN response. This is partially achieved through the IFN-mediated activation of negative regulatory factors that help in termination of the IFN response and return to a normal homeostatic state. Such built-in negative regulatory mechanisms are frequently hijacked by viruses such as the Hepatitis C virus (HCV) to increase viral replication and productive infections. We and others have shown that long non-coding RNAs (lncRNAs) play prominent roles in regulation of the IFN response. Activation of the IFN cascade alters the expression of a large number of lncRNAs, many of which are directly induced by the JAK/STAT pathway and thus, resemble the well-studied protein-coding interferon-stimulated genes (ISGs). While only a handful of IFN- and virally induced lncRNAs have been characterized, recent studies have identified several lncRNAs that act as positive or negative regulators of expression of ISGs during the IFN response. A number of such regulatory lncRNAs have multiple ISG targets, while others act on a single neighboring ISG. Another group of studied lncRNAs act further upstream and regulate the expression of IFN genes or factors that sense the presence of viral genome or replication products. The large number of unstudied IFN- and virally induced lncRNAs makes it highly likely that future studies will reveal a much greater share for this class of transcripts in regulation of the antiviral response. In addition to their physiological roles, the expression of such lncRNAs is frequently modulated by virally encoded factors to interfere with the antiviral response and promote viral replication, thus making them ideal targets for therapeutic intervention.